2017
DOI: 10.1627/jpi.60.301
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodesulfurization, Hydrodenitrogenation and Hydrodearomatization over CoMo/SAPO-11-Al<sub>2</sub>O<sub>3</sub> Catalysts

Abstract: Several SAPO-11-Al2O3 supports with different amounts of SAPO-11 were used to prepare a series of CoMo/ SAPO-11-Al2O3 catalysts by the impregnation method with or without addition of citric acid. Hydrodesulfurization (HDS) of 4,6-dimethyldibenzothiophene, hydrodenitrogenation (HDN) of acridine, and hydrodearomatization (HDA) of o-xylene, 1-methylnaphthalene and phenanthrene were carried out to evaluate the catalytic activity of the catalysts. The catalysts were characterized by BET, XRF, NH3-TPD, XPS and TEM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Panels g and h of Figure provide high-resolution XPS spectra of Mo 3d and Se 3d, respectively. In Figure g, Mo 3d 3/2 and 5/2 peaks are located at 231.8 and 228.7 eV, respectively, suggesting the existence of Mo 4+ in MoSe 2 . Nevertheless, unlike pristine MoSe 2 , Mo 6+ peaks gradually arose in Ar 2+ -5e14 and Ar 2+ -5e15, indicating the high oxidation state caused by the increasing dangling bonds of Mo atoms .…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Panels g and h of Figure provide high-resolution XPS spectra of Mo 3d and Se 3d, respectively. In Figure g, Mo 3d 3/2 and 5/2 peaks are located at 231.8 and 228.7 eV, respectively, suggesting the existence of Mo 4+ in MoSe 2 . Nevertheless, unlike pristine MoSe 2 , Mo 6+ peaks gradually arose in Ar 2+ -5e14 and Ar 2+ -5e15, indicating the high oxidation state caused by the increasing dangling bonds of Mo atoms .…”
mentioning
confidence: 93%
“…In Figure 1g, Mo 3d 3/2 and 5/2 peaks are located at 231.8 and 228.7 eV, respectively, suggesting the existence of Mo 4+ in MoSe 2 . 36 Nevertheless, unlike pristine MoSe 2 , Mo 6+ peaks gradually arose in Ar 2+ -5e14 and Ar 2+ -5e15, indicating the high oxidation state caused by the increasing dangling bonds of Mo atoms. 37 A similar phenomenon was also observed in Se, where the peaks sites of Se 3d 3/2 and 1/2 shifted to the higher binding energy (from 53.…”
mentioning
confidence: 95%
“…In our previous study, to clarify the correlation between the morphology of active slabs and catalytic activity, we focused on the interaction of active metal and support of the catalyst. Since the acidity of the support is expected to affect the hydrogenation activity, , by addition of SAPO-11, a zeolite with a large amount of weak acid sites, to an Al 2 O 3 support of the CoMo catalyst, we found that the formation of HDS, HDN, and HDA active phases was dramatically affected by improvement of the surface of the support . Incidentally, both HDS and HDA activities decreased with the addition of SAPO-11.…”
Section: Introductionmentioning
confidence: 77%
“…The loading amount of MoO 3 and CoO were determined by XRF measurement using Rayny EDX-700/800XRF analyzer (Shimadzu Co.). A 200 mg portion of catalyst samples was crushed and then compression molded into a shaped disk before obtaining an analyzing system …”
Section: Methodsmentioning
confidence: 99%
“…The loading amounts of CoO, MoO3, and TiO2 were determined by X-ray fluorescence (XRF) measurement using a Rayny EDX13 700/800XRF analyzer (Shimadzu Corp.). Catalyst samples 200 mg were crushed, then compression molded into a shape disk before analyzing 23) .…”
Section: Characterization Of Catalystsmentioning
confidence: 99%